Graphene Oxide-Based Membranes Intercalated with an Aromatic Crosslinker for Low-Pressure Nanofiltration - Hyuntak Kwon; Yongju Park; Euntae Yang; Tae-Hyun Bae (Membranes, 2022)
Graphene oxide (GO), a carbonaceous 2D nanomaterial, has received significant interest as a next-generation membrane building block. To fabricate high-performance membranes, an effective strategy involves stacking GO nanosheets in laminated structures, thereby creating unique nanochannel galleries. One outstanding merit of laminar GO membranes is that their permselectivity is readily tunable by tailoring the size of the nanochannels. Here, a high-performance GO-based nanofiltration membrane was developed by intercalating an aromatic crosslinker, α,α/-dichloro-p-xylene (DCX), between the layers in laminated GO nanosheets. Owing to the formation of strong covalent bonds between the crosslinker and the GO, the resulting GO laminate membrane exhibited outstanding structural stability. Furthermore, due to the precisely controlled and enlarged interlayer spacing distance of the developed DCX-intercalated GO membrane, it achieved an over two-fold enhancement in water permeability (11 ± 2 LMH bar−1) without sacrificing the rejection performance for divalent ions, contrary to the case with a pristine GO membrane.